LINGUOCULTURAL IMPROVISATION: A FRAMEWORK FOR ADAPTIVE CROSS-CULTURAL COMMUNICATION (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article introduces and explores the concept of linguocultural improvisation as an emerging framework for understanding adaptive cross-cultural communication. In today's interconnected global environment, traditional approaches to intercultural communication that rely heavily on predetermined cultural knowledge and communication protocols have proven insufficient for navigating the dynamic and unpredictable nature of authentic intercultural encounters. Drawing on research from sociolinguistics, cultural intelligence studies, communication theory, and performance arts, this paper conceptualizes linguocultural improvisation as the spontaneous, creative adaptation of linguistic and cultural elements during intercultural interactions. The article proposes a multidimensional framework consisting of four key components: contextual awareness, pragmatic flexibility, cultural sensitivity, and linguistic adaptability. Through analysis of empirical examples from diverse settings including international education, diplomatic exchanges, and multinational business environments, the research demonstrates how linguocultural improvisation enhances communicative outcomes and fosters more authentic cross-cultural relationships. The article concludes with implications for intercultural communication training and language education, proposing a developmental model for cultivating linguocultural improvisation capabilities.